Increased ASF1B Expression Correlates With Poor Prognosis in Patients With Gliomas - Zhu, Huaxin; Ouyang, Hengyang; Pan, Xinyi; Zhang, Zhixiong; Tan, Jiacong; Yu, Nianzu; Li, Meihua; Zhao, Yeyu (Frontiers in Oncology, 2022)
Background: Recent studies have shown that Anti-silencing function 1 B(ASF1B) may be a new potential marker of tumor prognosis. But the expression and function of ASF1B in gliomas remains to be determined. Herein, the aim of our study was to investigate the exact role of ASF1B in gliomas. Methods: Transcriptomic expression data were collected from the Cancer Genome Atlas database (TCGA), genotypic tissue expression (GTEx), Chinese Gliomas Genome Atlas databases(CGGA). The relationship between clinical variables and ASF1B was analyzed with the univariate and multivariate Cox regression. The ASF1B expression associated with overall survival (OS) was evaluated using Cox regression and the Kaplan–Meier method. Gene ontology (GO) analysis, gene set enrichment analysis (GSEA), and single-sample GSEA (ssGSEA) were performed using TCGA data. Results: ASF1B was highly expressed in glioma tissues. The Kaplan–Meier survival curve revealed a significant relationship of high expression of ASF1B with poor OS in patients with gliomas. Receiver operating characteristic (ROC) analysis showed that ASF1B may serve as a potential diagnostic biomarker for gliomas patients. Multivariate analysis showed that high ASF1B expression was an independent prognostic factor of OS in TCGA (HR = 1.573, 95% CI: 1.053–2.350, p = 0.027). Functional enrichment analysis found that ASF1B expression was associated with nuclear division, cell cycle, m-phase, cell cycle checkpoints. Base on ssGSEA analysis, ASF1B had a positive relationship with Th2 cells, macrophages, and aDC and while had a negative relationship with pDC, TFH, and NK CD56 bright cells. Conclusion: This study demonstrated that the increased expression level of ASF1B was significantly associated with the poor progression of gliomas and could serve as a novel prognostic biomarker for patients with gliomas.